Penyuluhan Mitigasi Risiko Penggunaan Listrik Rumah Tangga kepada Warga Perumahan Berkah Family Village - Maharmi, Benriwati; Ramdha, Triana; Arya, Engla Harda (JURNAL ABDIMAS DOSMA (JAD), 2025)
Berkah Family Village (BFV) is a residential community, which they have consumed large the electricity usage but low awareness of household electrical safety. This community service program aimed to enhance residents’ knowledge of safe electricity practices. The activity was conducted through three stages: initial observation, participatory educational sessions, and practical demonstrations, including safe device usage and short-circuit response simulations. Evaluation using pre- and post-activity questionnaires revealed a significant improvement in understanding, with over 85% of participants able to identify safe electrical equipment and basic emergency procedures. The program also fostered active participation and a stronger commitment among residents to implement safer and more responsible electricity use in their homes. These results highlight the effectiveness of community-based education in reducing household electrical risks.